Training Load and Performance Monitoring, Recovery, Wellbeing, Illness and Injury Prevention - Clemente, Filipe; Castillo, Daniel; Los Arcos, Asier (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book represents the efforts of different authors to analyze and provide solid evidence that supports training regulations based on monitoring strategies. This Special Issue includes original articles with some diversity, i.e., considering that different age groups, competitive levels, expertise, and conditions were researched regarding the main topics of training load and performance monitoring, recovery, wellbeing, and illness and injury prevention. Psychophysiological aspects were considered, as were locomotor and mechanical demands and tactical responses. The myriad outcomes analyzed present the reader with an overview of the state of the art and possible new directions for future research. In this book, readers will be also able to find systematic reviews about the key topics.